2018
DOI: 10.1103/physreve.98.060102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical criticality in open systems: Nonperturbative physics, microscopic origin, and direct observation

Abstract: Driven diffusive systems may undergo phase transitions to sustain atypical values of the current. This leads in some cases to symmetry-broken space-time trajectories which enhance the probability of such fluctuations. Here we shed light on both the macroscopic large deviation properties and the microscopic origin of such spontaneous symmetry breaking in the open weakly asymmetric exclusion process. By studying the joint fluctuations of the current and a collective order parameter, we uncover the full dynamical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 85 publications
2
23
0
Order By: Relevance
“…Instead of taking a limit where the system size goes to infinity, we utilize a recently introduced formalism [62] where N , the maximum number of particles in the box, is arbitrarily large. Applying the saddle-point method, it is shown that even such models can exhibit DPTs induced by the breaking of the particle-hole symmetry, which was theoretically predicted [44,45] and numerically observed [63] in extended systems, with exactly the same critical exponents. Importantly, the reduced dimensionality of a single-box model allows us to easily predict and confirm the effects of finite time, T , and finite size, N , on the critical phenomena near a symmetrybreaking DPT for arbitrary hopping rates.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Instead of taking a limit where the system size goes to infinity, we utilize a recently introduced formalism [62] where N , the maximum number of particles in the box, is arbitrarily large. Applying the saddle-point method, it is shown that even such models can exhibit DPTs induced by the breaking of the particle-hole symmetry, which was theoretically predicted [44,45] and numerically observed [63] in extended systems, with exactly the same critical exponents. Importantly, the reduced dimensionality of a single-box model allows us to easily predict and confirm the effects of finite time, T , and finite size, N , on the critical phenomena near a symmetrybreaking DPT for arbitrary hopping rates.…”
Section: Introductionmentioning
confidence: 71%
“…which is identical to (63). It is straightforward to show that other choices of dominating terms in Eq.…”
Section: Derivation Of the Scaling Theorymentioning
confidence: 86%
See 1 more Smart Citation
“…This singular change can be rationalized as a second-order DPT where timetranslation symmetry is broken [3,4,6,16,22,26]. Similarly, systems with particle-hole symmetry may exhibit regimes of current fluctuations where the dominant trajectory (or dynamical ground state as termed in the introduction) breaks such particle-hole invariance [38,44,47].…”
Section: The Statistical Physics Of Trajectoriesmentioning
confidence: 97%
“…Additionally, its microscopic origin is not understood yet and, most importantly, such a DPT has never been observed in numerical experiments, which might offer clues on novel phenomenology far from the critical point not yet explored. To shed light on all these issues, we have thoroughly studied the open 1d WASEP using both MFT and cloning Monte Carlo simulations in search of this elusive DPT [47].…”
Section: Particle-hole Symmetry Breaking At the Fluctuation Levelmentioning
confidence: 99%